2020
DOI: 10.1021/acsomega.0c02355
|View full text |Cite
|
Sign up to set email alerts
|

Juglans Sporopollenin for High-Performance Supercapacitor Electrode Design

Abstract: Recently, plant pollen has been used as a source of activated carbon to produce carbon-containing supercapacitor electrodes. However, in this study, pollen was used as a biotemplate with a completely different approach. As a biotemplate, pollen offers a wide range of varieties in terms of exterior, porosity, shape, and size. An electrode formed by the use of metal oxide grown on the pollen exine layer (sporopollenin microcapsules) as the active substance will inevitably exhibit good electrochemical capacitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
(68 reference statements)
0
8
1
Order By: Relevance
“…Black walnut sporopollenin shells had a significantly higher ( p < 0.001, one-way ANOVA) specific surface area than sporopollenin shells of other species. This result of the surface area of black walnut contradicts a recent report, where Atalay et al reported a much lower surface area (1.59 m 2 /g) and a different adsorption isotherm for black walnut sporopollenin shells. Specifically, the adsorption isotherm reported by Atalay et al showed a lack of a characteristic capillary condensation phenomenon associated with sporopollenin shells.…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…Black walnut sporopollenin shells had a significantly higher ( p < 0.001, one-way ANOVA) specific surface area than sporopollenin shells of other species. This result of the surface area of black walnut contradicts a recent report, where Atalay et al reported a much lower surface area (1.59 m 2 /g) and a different adsorption isotherm for black walnut sporopollenin shells. Specifically, the adsorption isotherm reported by Atalay et al showed a lack of a characteristic capillary condensation phenomenon associated with sporopollenin shells.…”
Section: Resultscontrasting
confidence: 92%
“…While a majority of the studies have reported a surface area of about 10 m 2 /g for sporopollenin shells isolated from pistachio pollen, 24 clubmoss spores, 25 and rape pollen, 26 others have reported a significantly higher (72 m 2 /g for date palm pollen) 27 or a significantly lower (1.59 m 2 /g for black walnut (BW) pollen) surface area. 28 This broad range of reported surface areas for sporopollenin shells prompted us to investigate the surface area of sporopollenin shells from a diverse pollen species to reach a conclusive agreement.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, phosphoric acid provides clean and less damaged SECs. 8 , 14 , 34 , 37 39 Therefore, phosphoric acid usage was preferred for its advantages in this study. For the acidolysis process, the precipitate was suspended in 200 mL of orthophosphoric acid in a 500 mL round-bottom flask.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Several acids such as hydrochloric acid, phosphoric acid, and sulfuric acid are used for the acidolysis step of SEC extraction. Among these, phosphoric acid provides clean and less damaged SECs. ,,, Therefore, phosphoric acid usage was preferred for its advantages in this study. For the acidolysis process, the precipitate was suspended in 200 mL of orthophosphoric acid in a 500 mL round-bottom flask.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Recently, plant pollen has been used as a source of activated carbon to produce carbon-containing supercapacitor electrodes. But, Atalay et al [28] has used pollen as a biotemplate through a completely different approach, which is differ from traditional process (Figure 4A). As a kind of biotemplate, pollen has a wide diversity in terms of appearance, porosity, shape and size.…”
Section: Biological Templatementioning
confidence: 99%